2018
DOI: 10.1186/s12863-018-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate genome-wide association analysis identifies novel and relevant variants associated with anterior cruciate ligament rupture risk in the dog model

Abstract: BackgroundAnterior cruciate ligament rupture (ACLR) is a debilitating and potentially life-changing condition in humans, as there is a high prevalence of early-onset osteoarthritis after injury. Identification of high-risk individuals before they become patients is important, as post-treatment lifetime burden of ACLR in the USA ranges from $7.6 to $17.7 billion annually. ACLR is a complex disease with multiple risk factors including genetic predisposition. Naturally occurring ACLR in the dog is an excellent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 84 publications
0
26
2
Order By: Relevance
“…SNPs with the largest mean difference were considered to be the most likely associated with ACL rupture (Hajiloo et al 2013). The number of genetic variants believed to affect ACL rupture in dogs is unknown, though there are likely hundreds to thousands of non-null effect SNPs (Baker et al 2017;Baker et al 2018). Therefore, prediction performance of each model was assessed at several SNP inclusion thresholds from 5 to 15,000 SNPs.…”
Section: Snp Selectionmentioning
confidence: 99%
“…SNPs with the largest mean difference were considered to be the most likely associated with ACL rupture (Hajiloo et al 2013). The number of genetic variants believed to affect ACL rupture in dogs is unknown, though there are likely hundreds to thousands of non-null effect SNPs (Baker et al 2017;Baker et al 2018). Therefore, prediction performance of each model was assessed at several SNP inclusion thresholds from 5 to 15,000 SNPs.…”
Section: Snp Selectionmentioning
confidence: 99%
“…CrCL ruptures continue to be a disease that negatively affects the lives of dogs who share our homes, as well as in working and sporting breeds. Advancing technology and facilities have reduced the costs of tests for the diagnosis of genetic and environmental components leading to CrCL rupture [10,11]. Although some studies [12] have reported a direct proportion between the incidence of CrCL rupture and increasing age, an increase in body weight and neutering rate have caused this disease to appear at an earlier age [13].…”
Section: Discussionmentioning
confidence: 99%
“…2014a, 2014b; Baker et al . 2017, 2018). The CCLR heritability estimate calculated for LRs using SNP genotype data was 0.493 (Baker et al .…”
Section: Program Heritability All Dogs (N = 333) Heritability With Sementioning
confidence: 99%